Laser system for recording optics - Semenets, V. V.; Neofitnyy, M. V.; Machekhin, Yu. P.; Hnatenko, O. S.; Zarytskyi, V. I.; Gulak, S. V. (CAOL, 2019)
The development of a modern laser system for recording optics is presented in this research paper. Studying optical components for designing this system by various methods, by calculated methods and by a method of using modern modeling package Zemax, was conducted. The results of the calculations and simulation, which led to the preliminary design of the laser system of optics registration, coincide.
Keywords: optical reflection; optical filters; optical sensors; stimulated emission; adaptive optics; lasers